Analisis Kinerja Dalam Konsep Hukum Perbankan dan Perkreditan - Ridha, Irfan; Saputra, Ilham Rahmat; Putri, Hernita; Fauzan, Khusnul; Ardiansyah, Jefri; Birawa, Julio Hafis Fakta; M, Mayarani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The function of the Bank is as a financial mediator that bridges between fund owners and people who need funds, both as depositors of funds and borrowers of funds. In the relationship between banks and customers, bank actions often occur which are detrimental to their customers, but so far legal protection is often not optimal, because in the relationship between banks and customers, it is seen that banks dominate banking transactions so that sometimes it is detrimental to customers. Based on the above facts, Law Number 21 of 2011 concerning the Financial Services Authority (UU OJK) has been promulgated. As a bank supervisory institution and as an institution that protects customer interests.